Taper and Volume Systems Based on Ratio Equations for Pinus pseudostrobus Lindl. in Mexico - García Espinoza, Guadalupe Geraldine; Aguirre Calderón, Oscar Alberto; Quiñonez Barraza, Gerónimo; Alanís Rodríguez, Eduardo; De Los Santos Posadas, Héctor Manuel; García Magaña, José de Jesús (Molecular Diversity Preservation International, 2018)
Studies on functional relationships between relative stem diameter and height to estimate timber yield are useful in the management of commercial forest plantations. With taper analysis data of 42 Pinus pseudostrobus Lindl. trees in the indigenous community of Nuevo San Juan Parangaricutiro , Michoacan, Mexico, six compatible systems for predicting taper (d), merchantable volume (Vm), stem volume (Vs), total tree volume (Vt) and branch volume (Vb) were fitted and evaluated. The compatible taper and merchantable volume equations were based on volume ratio equations. Three Vs equations were tested in each system. In general, the compatible systems presented statistical accuracy in the d, Vm, Vs and Vt components but were less accurate in Vb. Three compatible systems were selected, according to their more efficient goodness-of-fit statistics, and a different total volume equation was incorporated into each system. The compatible systems based on volume ratio equations are simple, reliable tools for estimation of stand timber stocks and product classification of P. pseudostrobus in commercial forest plantations in Mexico. Keywords: taper volume; compatible equation; stem volume; branch volume; total tree volume